Government responses to social-ecological impacts of “dzud” in Mongolia - Barnevik Olsson,Markus (2020)
“Dzud” is a unique winter weather phenomenon with devastating effects on livestock and the people of Mongolia. As climate change continues to intensify, the social-ecological impacts of dzud worsens. This qualitative case study analyses the Mongolian government’s response to dzud and its following social-ecological impacts from second-hand material. A measuring instrument based on social-ecological resilience theory was designed to answer the research question. By applying process tracing as an analytical framework, each time-period of 1999-2010 and 2010-2016 are analysed, respectively. This bachelor thesis aims at developing social-ecological resilience theory by providing an instrument capable of measuring the extent to which social-ecological resilience has been strengthened by government measures. There is little research on dzud, especially of the qualitative kind, and this thesis highlights the interplay between human and natural systems synchronously as it contributes to a limited research area. Results concluded that social-ecological resilience was strengthened to a relatively high extent during both time-periods.
Keywords: Mongolia; dzud; social-ecological resilience; environmental governance; process tracing